"أثر العدالة التنظيمية على الانتماء التنظيمي في المؤسسة الاقتصادية " - خولة, خراز; غنية, بسي; نجوى, مولاتي; هناء, خلوط (University of eloued جامعة الوادي, 2021)
"الملخص: هدفت الدراسة إلى معرفة أثر العدالة التنظيمية بأبعادها الثلاثة التوزيعية والإجرائية والتعاملية على الانتماء التنظيمي بالمؤسسة الوطنية لتوزيع الكهرباء والغاز بالوادي. طبقت الدراسة على عينة عشوائية طبقية بلغت 41 استبيانا قابلا للتحليل. واعتمدنا على المنهج الوصفي التحليلي للإجابة على إشكالية الدراسة والوصول إلى أهدافها واختبار فرضياتها، كما جرى تحليلها باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية،SPSS21) ), وتم تحليل البيانات باستخدام مجموعة من الاساليب الإحصائية (المتوسط الحسابي، الانحراف المعياري, معاملات الارتباط....الخ) في الأخير توصلنا إلى جملة من النتائج من أهمها: - مستوى إدراك العدالة التوزيعية في المؤسسة محل الدراسة عال؛ - مستولى إدراك الانتماء التنظيمي لدى أفراد العينة مرتفع؛ - توجد علاقة ذات دلالة إحصائية بين العدالة التنظيمية والانتماء التنظيمي؛ - لا توجد فروقات ذات دلالة إحصائية بين أفراد العينة تعزى إلى المتغيرات الشخصية؛ في الأخير نؤكد على ضرورة تدارك الضعف في محتوى إدراك كل من العدالة الإجرائية والتعاملية؛ ""Abstract: The study aimed to know the impact of organizational justice in its three dimensions, distributive, procedural and transactional, on organizational affiliation with the National Corporation for Electricity and Gas Distribution in the Valley. The study was applied to a stratified random sample of 41 analyzeable questionnaires. We relied on the descriptive analytical approach to answer the study problem, reach its objectives and consider its hypotheses, as they were analyzed using the Statistical Package for Social Sciences (SPSS21), and the data were analyzed using a set of probabilistic methods (arithmetic mean, standard deviation, correlation coefficients … etc.) Finally, we reached a number of results, the most important of which are: - The high level of awareness of distributive justice in the institution under study. - The high level of awareness of organizational affiliation among the sample members. - There is a statistically significant relationship between organizational justice and organizational affiliation. - There are no statistically significant differences between the sample members due to personal variables. "
ماستر ادارة اعمال
Keywords: العدالة التنظيمية، العدالة التوزيعية، العدالة الإجرائية، العدالة التعاملية، الانتماء التنظيمي; organizational justice, organizational affiliation, distributive justice, procedural justice, transactional justice.